The intra- and inter-variability of menstrual cycles in professional female footballers; the use of daily hormone measurements to determine ovulation - Anderson, R.; Rollo, I.; Martin, D.; Burden, R.; Randell. R. K.; Twist, C.; Grazette, N.; Moss, S. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Menstrual cycle (MC) variability exists in the general population [1], but it`s variability within athletic populations has not been reported. Advances in technology enabling a practical method of assessing daily reproductive hormone concentrations provide an avenue for such research. Accurate determination of ovulation is necessary to identify follicular (FP) and luteal phase (LP) lengths, which are pivotal to assess the impact of the MC on performance and health metrics [2]. Although a range of methods have been proposed to assess ovulation day and subsequent MC variability, agreement between methods remains unknown. Hence, the first aim of this study was to compare three methods of determining ovulation: (1) positive urinary luteinising hormone (LH) test, (2) sustained rise in progesterone above critical difference, and (3) countback regression equation (CRE). The second aim was to assess the variability in MC length, phase length, and concentrations of oestradiol and progesterone for each method.